Impact of T cell characteristics on CAR-T cell therapy in hematological malignancies - Tao, Zhongfei; Chyra, Zuzana; Kotulová, Jana; Celichowski, Piotr; Mihályová, Jana; Charvátová, Sandra; Hájek, Roman (Blood cancer journal, 2024)
Chimeric antigen receptor (CAR) T-cell therapy has revolutionized the treatment paradigms for hematological malignancies. However, more than half of these patients cannot achieve sustainable tumor control, partially due to the inadequate potency of CAR-T cells in eradicating tumor cells. T cells are crucial components of the anti-tumor immune response, and multiple intrinsic T-cell features significantly influence the outcomes of CAR-T cell therapy. Herein, we review progressing research on T-cell characteristics that impact the effectiveness of CAR-T cells, including T-cell exhaustion, memory subsets, senescence, regulatory T-cells, the CD4+ to CD8+ T-cell ratio, metabolism, and the T-cell receptor repertoire. With comprehensive insight into the biological processes underlying successful CAR-T cell therapy, we will further refine the applications of these novel therapeutic modalities, and enhance their efficacy and safety for patients.
Keywords: hematologické nádory; Immunotherapy, Adoptive; T-lymfocyty; chimerické antigenní receptory; Receptors, Chimeric Antigen; Humans; imunoterapie adoptivní; lidé; Hematologic Neoplasms; T-Lymphocytes